2000
DOI: 10.1002/1098-108x(200012)28:4<415::aid-eat9>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Mizes Anorectic Cognitions questionnaire‐revised: Psychometric properties and factor structure in a large sample of eating disorder patients

Abstract: Objective: This project was designed to develop and test the psychometric properties and factor structure of a revision of the Mizes Anorectic Cognitions questionnaire (MAC). The goals of the revision were to improve the reliability and discriminant validity of the Weight and Approval subscale and to equalize the length of the three subscales. Also, the study compared the original MAC and the MAC-R in terms of their psychometric properties. Method: Twenty-four new items were developed for potential inclusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Mizes Anorectic Cognitions Questionnaire-Revised (MACS-R: Mizes et al 2000). Eating cognitions were assessed using the 24-item MACS-R.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mizes Anorectic Cognitions Questionnaire-Revised (MACS-R: Mizes et al 2000). Eating cognitions were assessed using the 24-item MACS-R.…”
Section: Methodsmentioning
confidence: 99%
“…Eating cognitions were assessed using the 24-item MACS-R. The MACS-R is a comprehensive measures of eating cognitions and has been shown to differentiate individuals with symptoms of disordered eating and controls (Mizes 1992), as well as other broader disordered eating scales such as the Eating Disorders Inventory (Garner and Olmsted 1984;Mizes et al 2000). The MACS-R has three subscales: weight and eating behavior are the basis of approval by others (Weight and Approval subscale), self control with respect to eating and weight behaviors are the basis of self esteem (SelfControl subscale) and the importance of valuing rigid weight regulation and fearing weight gain (Rigid Weight Regulation subscale).…”
Section: Methodsmentioning
confidence: 99%
“…Disordered eating cognitions are multi-dimensional and include the fear of gaining weight, perceived importance of having an ideal weight and shape as a means of being accepted by others, and perceived self-worth related to self-control over diet and weight (Fairburn 2008;Fairburn et al 2003;Mizes et al 2000). In both clinical and non-clinical samples, research has demonstrated that these cognitions are associated with disordered eating behaviors (Miller et al 2009), general psychological distress Stice et al 1998), and help-seeking behaviors and attitudes (e.g., Cramer 1999; Mond et al 2009).…”
Section: Disordered Eating Cognitionsmentioning
confidence: 99%
“…The Mizes Anorectic Cognitions Questionnaire-Revised (MAC-R; Mizes et al 2000) is a 24-item self-report questionnaire designed to assess distorted cognitions related to all eating disorders. The cognitions involved are the fear of weight gain (e.g., "When I see someone who is overweight, I worry that I will be like him/her"), the importance of being thin or attractive to be socially accepted ("No one likes fat people; therefore, I must remain thin to be liked by others"), and self-esteem based on controlled eating habits and weight gain ("If my weight goes up, my self-esteem goes down").…”
Section: Disordered Eating Cognitionsmentioning
confidence: 99%
See 1 more Smart Citation